PENGARUH KEPUASAN KERJA DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI PADA KANTOR IMIGRASI KELAS II NON TPI KALIANDA - Tania Permata Yanra; Ni Putu Widhia Rahayu (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study examines the direct and indirect effects of job satisfaction and workload on employee performance, with work motivation serving as a mediating variable, at the Class II Non-Border Checkpoint Immigration Office (Non-TPI) in Kalianda. The study is motivated by increasing public service demands, the growing complexity of employees’ responsibilities, and the need to effectively manage job satisfaction, workload, and work motivation to enhance organizational performance. The proposed conceptual framework is grounded in Herzberg’s Two-Factor Theory and Vroom’s Expectancy Theory, which provide a theoretical basis for explaining the relationships among job satisfaction, workload, work motivation, and employee performance. A quantitative approach with an explanatory research design was employed. The study involved all 50 employees of the Class II Non-TPI Immigration Office in Kalianda, using a census sampling technique in which the entire population was included as respondents. Data were collected through a structured questionnaire based on a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The findings reveal that job satisfaction has a positive and significant effect on both work motivation and employee performance, whereas workload has a negative and significant effect on work motivation and employee performance. In addition, work motivation positively and significantly influences employee performance and partially mediates the relationships between job satisfaction and employee performance as well as between workload and employee performance. These findings suggest that improving employee performance requires organizations to enhance job satisfaction and strengthen work motivation while maintaining a balanced and manageable workload. Accordingly, management should prioritize fair reward systems, supportive leadership, continuous employee development, equitable task allocation, realistic performance targets, and the provision of adequate work resources to foster sustainable organizational performance.